NILAI PENDIDIKAN KARAKTER DAN RELEVANSINYA TERHADAP KETERAMPILAN ABAD XXI DALAM INTERPRETASI LORO BLONYO - Uji Windiatmoko, Doni (TARBIYA ISLAMIA : Jurnal Pendidikan dan Keislaman, 2020)
ABSTRACT The purpose of this article is to describe the interpretation of the Loro Blonyo statue in a Javanese traditional house. The statue is a transformation of the teaching of Manunggaling Kawula Gusti. This research is a literature study. On the other hand, loro blonyo contains the value of character education that is relevant to XXI Century Skills. The research method in the form of literature study. The results showed that the placement of the Loro Blonyo statue was a representation of Manunggaling Kawula Gusti teachings. The loro blonyo statue and Javanese traditional house emphasize the importance of harmony. Placement of the statue which is placed in the middle senthong commonly called pasren, reflects the focal point of the meeting of the two lines. The vertical line as a form of human servitude to God, while the horizontal line is the collectivity of human relationships with others and the natural surroundings. The loro blonyo statue is also a figure from the form of kawula, while the joglo house is a channel to the highest place, God. The statue of a pair of bride and groom is placed side by side so that the souls of Dewi Sri and Raden Sadhana are present in the house to provide happiness, prosperity, and new life (fertility). The value of character education obtained is religious value, tolerance, democratic, social care, and care for the environment. Meanwhile, for the XXI century skills that can be described are learning and innovation skills, digital literacy skills, and life skills and career skills.   Keywords: Loro Blonyo?s Statues; Manunggaling Kawula Gusti; Character Education; XXI Century Skills